If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -2y = -22 + y Solving 2 + -2y = -22 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 2 + -2y + -1y = -22 + y + -1y Combine like terms: -2y + -1y = -3y 2 + -3y = -22 + y + -1y Combine like terms: y + -1y = 0 2 + -3y = -22 + 0 2 + -3y = -22 Add '-2' to each side of the equation. 2 + -2 + -3y = -22 + -2 Combine like terms: 2 + -2 = 0 0 + -3y = -22 + -2 -3y = -22 + -2 Combine like terms: -22 + -2 = -24 -3y = -24 Divide each side by '-3'. y = 8 Simplifying y = 8
| Blank+blank=936 | | -8x-3=-9x+4 | | x+2(x+4)=66 | | 8x+2x-17+10-5x+20=100 | | 3xy-5a=9b | | b-9+7b=24 | | k-6+12k=7-8k+9-k | | 2(x+5)=2(x-5) | | -8n+(1+5n)=-6n | | K+0.6=3.84 | | -x-3=3x+33 | | (8m-8n)(4m-7n)= | | 8x+7x-88=110-7x | | -3x-(-5)+2x=-x-4 | | 1+5x-40=1x-5 | | x+x+4=36 | | -10+x+4-4-5=7x-5 | | 6x+2(7x-4)=92 | | x+2y=29 | | -3x+8=18+4x | | x+2x=62 | | x-3(x-4)+2=14-3(5x+6) | | 3*n-8=2*n+15 | | 4(6x+3x)=12 | | 60k+60k=50k+100 | | x+x+2=62 | | -9+2.5y-.7y+1+6.4y= | | 2.4x=4x-88 | | X^2+5x=46 | | xy-d=mfory | | -18+9x=63 | | 2(x+4)+3(-x)=2(-x) |